ANALISIS POLA SEGREGASI DNA GENOM KLOROPLAS HASIL HIBRIDISASI SOMATIK TANAMAN KENTANG MENGGUNAKAN TEKNIK RAPD (RANDOM AMPLIFIED POLYMORPHIC DNA) - Sudirman Numba (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2017)
Segregation pattern of the chloroplast genome in somatic hybridization potato between S. tuberosum cv. BF-15 and the wild species of S. stenotomum was identified through RFLP analysis in 3.2 kb fragment produced from PCR amplification for specific regions of DNA chloroplast. PCR amplification was performed by using rbcL primer and ORF106, i.e. specific primer located on konsenrvatiive sequence which flanking 3.2 kb fragment region of DNA chloroplast. PCR amplification product used two primers, in conformity with the target region on DNA chloroplast, where generated fragments or DNA bands with a size of about 3.2 kb. The 3.2 kb fragment produced from amplification was cut by using two kinds of restriction enzymes HhaI and RSAI.  Restriction Enzym treatment with HhaI resulted in four bands each measuring; those were 2.0 kb, 1.2 kb, 0.8 kb and 0.4 kb. While the treatments by using RSAI restriction enzymes, also resulted in four bands each measuring, those were 1.6 kb, 0.7 kb, 0.3 kb and 0.2 kb. Band pattern that produced from restriction enzyme showed that monomorphic nature or not polymorphic at all elder fusion plant, so this method can not be used to identify the patterns of chloroplast genome segregation in plant which is produced by somatic hybridization.